2020
DOI: 10.1002/jbm4.10395
|View full text |Cite
|
Sign up to set email alerts
|

Physical Function and Health‐Related Quality of Life in Adults Treated With Asfotase Alfa for Pediatric‐Onset Hypophosphatasia

Abstract: Hypophosphatasia (HPP) is a rare, inherited, metabolic disease characterized by tissue‐nonspecific alkaline phosphatase deficiency resulting in musculoskeletal and systemic clinical manifestations. This observational study evaluated the effectiveness of enzyme replacement therapy with asfotase alfa on physical function and health‐related quality of life (HRQoL) among adults with pediatric‐onset HPP who received asfotase alfa for 12 months at a single center (http://ClinicalTrial.gov no.: NCT03418389). Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
1
22
1
1
Order By: Relevance
“…Recent studies have shown the effectiveness of asfotase alfa treatment in adults and adolescents with pediatric-onset HPP, showing an improvement of osseous consolidation of non-unions [ 119 ], a normalization of circulating TNSALP substrate levels, and improved functional abilities and health-related quality of life [ 119 , 120 , 121 ], without severe adverse events.…”
Section: Treatment Of Hppmentioning
confidence: 99%
“…Recent studies have shown the effectiveness of asfotase alfa treatment in adults and adolescents with pediatric-onset HPP, showing an improvement of osseous consolidation of non-unions [ 119 ], a normalization of circulating TNSALP substrate levels, and improved functional abilities and health-related quality of life [ 119 , 120 , 121 ], without severe adverse events.…”
Section: Treatment Of Hppmentioning
confidence: 99%
“…Further screening for additional candidates with higher selectivity and potency identified a second inhibitor, SBI-425, which is more appropriate for in vivo applications [ 101 ]. SBI-425 has been used in several studies related to vascular calcification [ 94 , 97 , 102 ] and by our own lab to identify its applicability for studying TNAP’s role in the brain. In collaboration with the developers of TNAPi and SBI-425, we demonstrated that the SBI-425 inhibitor is unable to cross the BBB in healthy mice [ 35 ].…”
Section: Models and Tools To Study Tnapmentioning
confidence: 99%
“…This drug works through the cleavage of inorganic pyrophosphate (PPi) to phosphate (Pi) so that Pi may bind with calcium to form hydroxyapatite crystals needed for healthy bones [ 48 , 105 , 106 ]. Overall, this treatment has shown to help improve physical function and health-related quality of life in adults with pediatric-onset HPP [ 102 ]. Recombinant human TNAP (rhTNAP) purified from rabbit transgenic milk samples and administered to LPS-infected mice resulted in increased survival [ 107 ].…”
Section: Models and Tools To Study Tnapmentioning
confidence: 99%
See 1 more Smart Citation
“…Alltagsmobilität, wie etwa dem Chair-Rise Test und dem 6-Minute Walk Test[20]. Interessant wird sein, im Verlauf zu verstehen, inwiefern dies wesentlich mit einer verbesserten Belastbarkeit des Knochens assoziiert ist oder aber auch indirekte Effekte auf die Muskulatur und andere Stoffwechselprozesse eine ursächliche Rolle spielen, etwa durch Veränderungen der Konzentration von Substraten oder durch zirkulierendes Enzym.…”
unclassified